MELANOTIC PIGMENTATION IN EXCISION SCARS OF MALIGNANT MELANOMA - THREE CASE REPORTS - Resende, Cristina (2015)
Introduction: The appearance of pigmented lesions in scars of malignant melanoma is a finding that worries dermatologists/dermatopathologists, because they are faced with the possibility of persistence/recurrence of malignant melanoma.Case reports: We present three cases of patients with melanocytic pigmentation in scars of malignant melanoma and discuss the clinical and histological aspects of these. In all cases, we observed macules similar to lentigo spots, but histologically we observed three different patterns: lentiginous epidermal hyperplasia, lentiginous hyperplasia of melanocytes and malignant melanoma in situ.Discussion: There are three types of pigmentation, which may arise in the scar of malignant melanoma: lentigo type lesions, pigmented streaks and diffuse pigmentation. Histologically, three patterns of melanocytic pigmentation in scars of malignant melanoma, are described: lentiginous epidermal hyperplasia, lentiginous hyperplasia of melanocytes and persistence/ recurrence of malignant melanoma. The scar appears to be responsible for pigmentation by a process of induction acting on epidermal melanocytes.